Circularly Polarized Absorption and Luminescence of Semiconductor Eu‐OCN Nanocrystals in the Blue Region of the Electromagnetic Spectrum. Issue 17 (19th August 2020) - Hasegawa, Yasuchika; Koide, Katsumasa; Tsurui, Makoto; Kitagawa, Yuichi; Nakanishi, Takayuki; Doi, Yoshihiro; Hinatsu, Yukio; Fushimi, Koji
Abstract: Semiconductor nanomaterials with efficient polarized‐light control in the blue region of the visible spectrum are promising candidates for modern and future photo‐information technology, display devices, and optical sensing applications. New‐type semiconductor Eu(OCN)2 nanocrystals with circularly polarized absorption (CD: circular dichroism) and emission (CPL: circularly polarized luminescence) under an applied magnetic field are demonstrated here for the first time. The effective CD signal at 1.6 T was observed at approximately 440 nm. The dissymmetry factor of CPL under 100 K, gM‐CPL, was estimated to be 0.01. These characteristic circularly polarized absorption and emission phenomena of Eu(OCN)2 nanocrystals should be caused by combination between the "Faraday A and C terms" of the magnetic moment in the excited state. Polarized‐light control using Eu(OCN)2 nanocrystals in the blue‐light region of the electromagnetic spectrum is a large first step into a new world of photo‐functional semiconductor nanomaterials. Abstract : Semiconductor nanomaterials with efficient polarized light control are promising candidates for future photo‐information technology and display devices. Novel semiconductor Eu(OCN)2 nanocrystals with circularly polarized absorption (CD) and circularly polarized luminescence (CPL) in the blue light region are reported. This finding may lead to the development of a novel area in the field of polarized‐light science and technology.